Targetting women and youth with inclusive CSA and CIS, 2021-2025: Gender and social inclusion in AICCRA by the numbers - Huyer, Sophia (2025)
AICCRA has evolved its approach to gender and social inclusion (GSI) from targeting women for inclusion in CSA and climate information, to one of integrating gender-responsive and -transformative approaches into inclusive CSA/CIS bundles and innovation packages. It has developed a set of frameworks for GSI, including CSA prioritization and consultation that enables women and youth, GSI analyses, the Gender Smart Agriculture approach that frames gender equality in relation to resilience, and the Gender and Climate Empowerment Index